Effect of maize hybrids on the biological characteristics of the fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), under laboratory conditions - M. A. M. Youssef; M. M. S. Bakry; N. F. Abdel-Baky (Brazilian Journal of Biology)
Abstract The fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), an invasive and polyphagous pest affecting various vital crops globally, was studied to assess how different maize hybrids impact its biological parameters under controlled laboratory conditions. Maize, a crucial crop for food security in Egypt, requires effective Integrated Pest Management (IPM) strategies to manage pests like S. frugiperda. This article explores how S. frugiperda performs on five maize hybrids—Hi-Tech 2031, Wataniya 6, Giza 10, Giza 128, and Giza 168. Significant differences were observed in larval duration across the hybrids, with the shortest duration (14.08 days) on Hi-Tech 2031. Giza 128 resulted in the longest pupal period (9.39 days), and adult lifespans varied between 8.91 and 9.61 days. Reproductive parameters also diverse, with pre-oviposition periods ranging from 4.64 to 4.90 days and oviposition periods from 3 to 4.14 days. The highest average egg count (1352.19 eggs) was recorded with Giza 10. Hybrids Hi-Tech 2031 and Giza 128 had a lower male proportion (44.81% and 43.45%, respectively). Giza 10 also yielded the highest pupation rate (93.33%), while Hi-Tech 2031 showed the highest emergence rate (96.33%).